2023
DOI: 10.3389/fmars.2023.1204598
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and metabolomics reveal the molecular and metabolic adaptation to heat stress in Manila clam Ruditapes philippinarum

Abstract: Temperature is an important environmental factor affecting metabolism, growth and life activities of marine bivalves. To reveal the molecular and metabolic responses to heat stress, comparative transcriptomics and metabolomics were performed in the commercially important bivalve, Manila clam Ruditapes philippinarum. Comparative transcriptomics revealed a total of 3980 differential genes (DEGs) mainly involved in energy metabolism, protein processing, glycerolphospholipid metabolism, inoxidizability and anti-ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 105 publications
0
0
0
Order By: Relevance
“…Temperature is an important environmental factor that affects the metabolism, growth, and life activities of marine bivalves [10]. When shellfish perceive short-term fluctuations in temperature or long-term seasonal changes, they will adapt to the change in the environmental temperature by actively adjusting their physiological and biochemical activities [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature is an important environmental factor that affects the metabolism, growth, and life activities of marine bivalves [10]. When shellfish perceive short-term fluctuations in temperature or long-term seasonal changes, they will adapt to the change in the environmental temperature by actively adjusting their physiological and biochemical activities [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the physical response mechanisms in various shellfish under changing environmental temperatures and have shown that the expression of heat shock proteins (HSPs) is stimulated in shellfish to maintain cell homeostasis under high temperature conditions, where the response to damage also involves the activation of immune cells and accelerated metabolism. Under low-temperature conditions, shellfish respond to oxidative stress by stimulating the production of glutathione S-transferases (GSTs), such as in Ruditapes philippinarum [10], Patinopecten yessoensis [12,13], and Chlamys farreri [13]. However, the regulatory mechanism that allows Neptunea cumingii to adapt to seasonal temperature changes has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%